Evaluating the Effectiveness of the Grade 12 English Textbook in Developing Communicative Competence in Muzaffarabad, AJ&K - Ahmed, Sobia; Sohail, Ayesha (Pakistan Languages and Humanities Review, 2024)
This study aims to evaluate the effectiveness of the Grade 12 English textbook prescribed by Khyber Pakhtunkhwa Board of Intermediate Studies to develop Oral communication skills of students in Muzaffarabad, Azad Jammu & Kashmir. The research examines how the textbook fosters key oral communication skills, including pronunciation, speaking, vocabulary, grammar, and real-life-based language use through structured activities. A mixed-method approach was employed using qualitative and quantitative tools including checklist questionnaires and thematic analysis. A sample of 200 students from five different government and private colleges from Muzaffarabad AJ&K was randomly selected. The findings revealed that classrooms and English lessons are largely teacher-centered with textbook taught traditionally limiting students’ oral communication skills. Based on the findings, it is recommended to integrate student centered and real-life interaction activities in the textbook and train the teachers in interactive and communicative methods to enhance oral communication skills of students.